2016
DOI: 10.5430/ijhe.v6n1p48
|View full text |Cite
|
Sign up to set email alerts
|

The Development, Validity, and Reliability of the Barriers to Seeking Psychological Help Scale for College Students

Abstract: The aim of this study was to develop a scale to determine the barriers affecting undergraduate students seeking psychological help. In line with this purpose, the validity and reliability of the scale were examined in five different samples. Exploratory factor analysis results suggested that the scale consists of five dimensions, labeled as fear of being stigmatized by society, trust in the mental health professional, difficulties in self-disclosure, perceived devaluation and lack of knowledge in the first sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 36 publications
0
15
0
1
Order By: Relevance
“…It is also known that because of the cultural significance of privacy, many immigrant groups are reluctant to talk about matters related to family problems or personal concerns (Chung & Bemak, 2007). It is also possible to mention the worry of being stigmatized as a common obstacle for individuals to get psychological help (Byrow et al, 2019;Shannon et al, 2015;Topkaya et al, 2017). Although this obstacle is a considerably common problem, it is known that it is highly influenced by cultural factors and conditions such as migration (Amri & Bemak 2012;Byrow et al, 2019;Nadeem et al, 2007;Topkaya, 2014;Yagan & Aksit, 2021;Zhang & Dixon, 2003).…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…It is also known that because of the cultural significance of privacy, many immigrant groups are reluctant to talk about matters related to family problems or personal concerns (Chung & Bemak, 2007). It is also possible to mention the worry of being stigmatized as a common obstacle for individuals to get psychological help (Byrow et al, 2019;Shannon et al, 2015;Topkaya et al, 2017). Although this obstacle is a considerably common problem, it is known that it is highly influenced by cultural factors and conditions such as migration (Amri & Bemak 2012;Byrow et al, 2019;Nadeem et al, 2007;Topkaya, 2014;Yagan & Aksit, 2021;Zhang & Dixon, 2003).…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…The goodness–of–fit of the five structures was determined using CFA. Studies suggested that a x 2 /df value less than 5 [ 79 ], a goodness–of–fit index (GFI) and confirmatory fit index (CFI) greater than 0.8 [ 80 ], and a root mean square error of approximation (RMSEA) less than 0.08 indicate good fit [ 81 ]. The five–factor model yielded the best fit with the data (x 2 /df = 3.67; RMSEA = 0.06; GFI = 0.82; CFI = 0.89).…”
Section: Methodsmentioning
confidence: 99%
“…Kondisi yang serupa juga diungkapkan oleh penelitian terdahulu seperti, Rasyida (2019) mengungkapkan bahwa faktor penghambat mahasiswa untuk menemukan bantuan psikologis yakni mahasiswa merasa masalah yang dialami bukan masalah yang serius, mahasiswa memiliki kerabat dekat yang dianggap masih dapat memberikan pertolongan pada saat memiliki permasalahan, dan faktor ketidaktahuan mahasiswa terkait dengan informasi bantuan psikologis. Kesulitan dalam mencari bantuan psikologis telah banyak ditemukan diberbagai negara pada penelitian terdahulu seperti penelitian (Ramdass et al, 2020;Topkaya, 2017;Czyz et al, 2013).…”
Section: Hasil Dan Pembahasanunclassified